Effects of Triaxiality and Radiation Pressure on Existence of Resonance Stability of Triangular Equilibrium Points in Elliptical Restricted Three-Body Problem - Pandey, Krishna Kumar; Narayan, A.; Shrivastava, Sandip Kumar (Journal of Informatics and Mathematical Sciences, 2019)
This paper deals with the effects of radiation and triaxiality on linear stability of the triangular librations points for small value of eccentricity ‘\(e\)’ in presence of resonance. The study is carried out for various values of radiation pressure and Triaxiality parameter of both Primaries. It is found that the parametric resonance is only possible at the resonance frequency \(ω_2 =1/2\) in elliptical case.